What Parents Need to Know About Vitamin K Administration at Birth. Issue 3 (June 2015) - Bellini, Sandra
Abstract Prophylactic treatment of newborns with intramuscular vitamin K has been the standard of care for many years in the United States. However, instances of parental refusal of routine prophylaxis are currently on the rise. Refusal of routine prophylaxis can have serious long‐term neurodevelopmental consequences for some newborns, who may subsequently develop vitamin K deficiency‐associated hemorrhagic disease of the newborn (HDN).